Answer:
x=60
Step-by-step explanation:
Simplifying
0.79x + 24 = 1.19x
Reorder the terms:
24 + 0.79x = 1.19x
Solving
24 + 0.79x = 1.19x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1.19x' to each side of the equation.
24 + 0.79x + -1.19x = 1.19x + -1.19x
Combine like terms: 0.79x + -1.19x = -0.4x
24 + -0.4x = 1.19x + -1.19x
Combine like terms: 1.19x + -1.19x = 0.00
24 + -0.4x = 0.00
Add '-24' to each side of the equation.
24 + -24 + -0.4x = 0.00 + -24
Combine like terms: 24 + -24 = 0
0 + -0.4x = 0.00 + -24
-0.4x = 0.00 + -24
Combine like terms: 0.00 + -24 = -24
-0.4x = -24
Divide each side by '-0.4'.
x = 60
Simplifying
x = 60